Análise da variabilidade do mtDNA na população brasileira - Juliana Alves da Silva (2000)
In the present study we characterised the maternal ancestry of 149 Brazilian individuals through an extensive analysis of mtDNA continent-specific polymorphisms. The samples came from three different geographic regions of Brazil, namely, North, Northeast and South regions, and represent mostly the white fraction of the Brazilian population. Associating hipervariable segment I sequencing analysis and RFLP tests we were able to determine the Amerindian, African or European origin for all of our samples with a high degree of confidence. Our results clearly showed a greater contribution of Amerindian mtDNA lineages in the Northern population, while the Northeast is characterised by the predominance of African lineages, and the European lineages are by far the most frequent in the South. The total sample presented 32% of Amerindian lineages, 24% of African, and 44% of European haplotypes. All of our samples were classified in one of the so called continent-specific mtDNA haplogroups described for Amerindian, African and European populations which were not even distributed across Brazil. Finally, our results seems to reflect different processes taken place in the formation of the present day white Brazilian population, like directional mating involving European (Portuguese) men and Native-American or African women since early of the colonisation time, as well as the recent immigrant waves from Europe of the last two centuries. The second part of this study is related to the characterisation of mtDNA lineages in archaeological samples from Brazil. Unfortunately our preliminary results of aminoacid racemization analysis demonstrated that those samples were not appropriate for ancient DNA retrieval and thus we decided not to continue with DNA extraction procedures in order to save samples which constitute important human remains of the "Lagoa Santa Man" population.